Implementasi Aplikasi Mobile Knowledge Management System pada PT. Pesona Edukasi menggunakan Pendekatan Rapid Application Development - Andi Seppewali; Farly Fitrian Dwiputra; Warseno Hari Mulyo (UNIVERSITAS STEKOM, 2024)
Effective knowledge management is crucial for maintaining competitiveness in today's digital era. PT. Pesona Edukasi, as a developer of educational software, faces challenges in managing and disseminating knowledge among their frequently mobile IT Helpdesk team. To address this, this research aims to implement a Mobile Knowledge Management System using the Rapid Application Development (RAD) approach at PT. Pesona Edukasi.The RAD method was chosen to enable rapid, flexible, and responsive application development to meet changing business and technological needs. This study includes needs analysis, system design, prototype development, and application evaluation to ensure its effectiveness in enhancing access and collaboration in knowledge dissemination throughout the company. The results of the research, following the application implementation, demonstrate a positive contribution to improving operational efficiency and IT service quality at PT. Pesona Edukasi, accelerating knowledge exchange and enhancing the productivity of the IT Helpdesk team.